Thermoplastic starch/biochar biocomposites produced by extrusion for controlled phosphorus release in agriculture - Paiva, Andressa Monteiro Castro (2025)
Global population growth has intensified the demand for phosphate fertilizers, as phosphorus (P) is essential for plant growth and traditionally derives from non-renewable mineral deposits, which are now in decline. The circular economy presents itself as a strategy for transforming agro-industrial waste into alternative nutrient sources. Fish scales, rich in minerals, are emerging as a raw material for biochar production, enabling the recovery of P for agricultural use. This study evaluated the feasibility of using biocomposites of biochar from tilapia (Oreochromis niloticus) scales with thermoplastic starch as a controlled-release fertilizer. The study also evaluated how extrusion can alter the chemical characteristics of P, increasing the available fraction. Biochar (BIO600°C) was produced by pyrolysis of scales in a muffle furnace at 600°C. Starch biocomposites containing 0% (AMI), 10% (AMI10), 20% (AMI20), and 30% (AMI30) biochar were processed in a twin-screw extruder with a thermal profile of 80 to 110°C. Fourier transform infrared spectroscopy (FTIR), thermogravimetry (TGA), scanning electron microscopy coupled with EDS (SEM-EDS), and point of zero charge (PCZ) were used to characterize the synthesized materials. Total and available P content was quantified by protection methods and spectrophotometry. P release kinetics was evaluated in vitro, and greenhouse tests evaluated the agronomic efficiency of the materials in wheat cultivation. SEM demonstrated the effective incorporation of biochar into the starch matrix, while FTIR spectra demonstrated the persistence of bonds characteristic of AMI and BIO600°C in the composites, interacting with chemical interactions favored by extrusion. TGA confirmed the biochar proportions and revealed an increase in the thermal stability of the biocomposites compared to pure starch. P content analyses showed that extrusion increased the available P content. In the kinetic analysis, BIO600°C presented a lower P release rate/time, while the composites released the nutrient more rapidly, predominantly by diffusion, as indicated by the fit to the Peppas–Sahlin model. In a greenhouse, the restrictions of wheat treated with BIO600°C are statistically similar to those of cereal treated with commercial fertilizer. Meanwhile, the soil treated with pure starch was characterized as acidic, impairing biogeochemical reactions important for wheat development. The results indicated that fish scale biochar constitutes a viable alternative for circular agriculture; however, the rapid release of biocomposites suggests the need for optimization of polymer matrices.